Measurement of aquatic competence in toddlers, infants, and children between 6 months and 14 years: a systematic review - Juárez Santos-Garcia, Daniel (2022)
The aim of this study was to carry out a systematic review of the literature on tools for measuring aquatic competence in toddlers, infants, and children between the ages of 6 months to 14 years old. A systematic review was carried out following the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) statement. Six of the eight studies selected obtained high valuations based on the Downs and Black Quality Assessment checklist. The studies were classified into three categories, one that proposed tools that measured actual aquatic competence (n=6), the other one that measured perceived aquatic competence (n=1), and the other that measured both (n=1). Five studies measured emotional, social, cognitive, and communicative skills apart from motor skills. Most of the studies focused the proposed assessment tool on a specific age group, while two looked at a broader age group. In conclusion, eight instruments have been developed and validated in recent years for measuring aquatic competence for children between 6 months and 14 years of age from a multipurpose perspective. These have tools designed to facilitate and improve teacher assessment and determine children's perception of their own aquatic competence.  Keywords: motor development; swimming skills; water skills; assessment.